Preterm birth and antidepressant medication use during pregnancy: a systematic review and meta-analysis. - Krista F Huybrechts; Reesha Shah Sanghani; Jerry Avorn; Adam C Urato (PLoS ONE)
Introduction Preterm birth is a major contributor to neonatal morbidity and mortality and its rate has been increasing over the past two decades. Antidepressant medication use during pregnancy has also been rising, with rates up to 7.5% in the US. The objective was to systematically review the literature to determine the strength of the available evidence relating to a possible association between antidepressant use during pregnancy and preterm birth. Methods We conducted a computerized search in PUBMED, MEDLINE and PsycINFO through September 2012, supplemented with a manual search of reference lists, to identify original published research on preterm birth rates in women taking antidepressants during pregnancy. Data were independently extracted by two reviewers, and absolute and relative risks abstracted or calculated. Our a priori design was to group studies by level of confounding adjustment and by timing of antidepressant use during pregnancy; we used random-effects models to calculate summary measures of effect. Results Forty-one studies met inclusion criteria. Pooled adjusted odds ratios (95% CI) were 1.53 (1.40-1.66) for antidepressant use at any time and 1.96 (1.62-2.38) for 3rd trimester use. Controlling for a diagnosis of depression did not eliminate the effect. There was no increased risk [1.16 (0.92-1.45)] in studies that identified patients based on 1st trimester exposure. Sensitivity analyses demonstrated unmeasured confounding would have to be strong to account for the observed association. Discussion Published evidence is consistent with an increased risk of preterm birth in women taking antidepressants during the 2nd and 3rd trimesters, although the possibility of residual confounding cannot be completely ruled out.